PENINGKATAN HASIL BELAJAR IPS MENGGUNAKAN METODE KERJA KELOMPOK KELAS V SDN 09 BENGKAYANG - Miran, Miran; Asran, Mastar; Tampubolon, Budiman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to describe the application of group work methods in improving social science learning outcomes of students grade V elementary school 09 Sujah Bengkayang. The research method used in this research is descriptive, the form of research that is classroom action research, the nature of research is collaborative. Subjects in this study are teachers and students of class V. Data collection techniques in this study is direct observation and measurement. This study was conducted as much as two cycles. The results of the research are (1) The ability of teachers in designing learning cycle I ie 3.43 (good) and cycle II of 3.78 (very good). (2) The ability of teachers in implementing learning in the first cycle is 3.09 (good) and cycle II of 3.86 (very good). (3) Student learning result by using group work method on social science learning in class V SD 09 Sujah on silus I equal to 74,08 and cycle II to 85,35. Conclusion in this research is social science learning using group work method can improve student learning result class V SD 09 Sujah,Bengkayang.Â Keywords: Group Work, Learning Outcomes, Social Science.